2015
DOI: 10.1186/s13550-015-0126-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immune cell markers in tumor tissue treated with radioimmunotherapy in an immunocompetent rat colon carcinoma model

Abstract: BackgroundImmune cells within the tumor can act either to promote growth or rejection of tumor cells. The aim of the present study was to evaluate immune cell markers (number and localization) within the tumor before and during rejection due to radioimmunotherapy, to determine whether there is a change in markers related to rejection and/or tolerance of the tumor cells.MethodsThirty immunocompetent rats were inoculated with syngeneic rat colon carcinoma cells and 13–14 days later 21 of these rats were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…These were mainly involved in processes of infiltration of immune cells and angiogenesis. The presence of chemokines promoting the recruitment of leukocytes corresponded with earlier studies showing infiltration of neutrophils, 9 T cells, and macrophages 10 in this tumor model. The cytokine pattern was considered to be neither pro-inflammatory (described as consisting of IL-6, IL-17, IFN-γ, TNF-α, IL-1α/β among others) nor anti-inflammatory (containing cytokines like IL-1ra, IL-14, IL-5, IL-10, IL-11, IL-13).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These were mainly involved in processes of infiltration of immune cells and angiogenesis. The presence of chemokines promoting the recruitment of leukocytes corresponded with earlier studies showing infiltration of neutrophils, 9 T cells, and macrophages 10 in this tumor model. The cytokine pattern was considered to be neither pro-inflammatory (described as consisting of IL-6, IL-17, IFN-γ, TNF-α, IL-1α/β among others) nor anti-inflammatory (containing cytokines like IL-1ra, IL-14, IL-5, IL-10, IL-11, IL-13).…”
Section: Discussionsupporting
confidence: 89%
“…9 Analysis of immune cell markers demonstrated that T cells and macrophages augmenting tumor rejection were present to a higher extent than those associated with immune tolerance, and that the number of immune cells decreased as a result of the treatment. 10 After treatment, approximately half of the animals in the syngeneic rat model developed metastases within the follow-up period of 100 days. The number of animals with metastases increased after the depletion of CD8-positive cells, 11 indicating that the immune system may be important in preventing the development of metastases.…”
Section: Introductionmentioning
confidence: 99%